PATHOGENETIC ASPECTS OF THE PROPERTIES OF WATER IN THE HUMAN BODY AND THE EFFECT OF SOLID WATER - Nurov Sarboz Azimovich (Scholar Express Journals, 2024)
The pathogenesis of groundwater with a high chemical composition is explained by the direct and indirect effects of chemicals on the body. Chemical compounds contained in water are associated with their direct and indirect effect on the vascular walls and in the parenchyma of whole organs, and on the metabolism. This is accompanied by a violation of physicochemical processes in the affected cells. In this case, the process of increasing or weakening the permeability of the cell membrane is observed
Keywords: Radiolysis of water; atomic hydrogen; hydroperoxyl radicals; hydrogen peroxide